2007
DOI: 10.1111/j.1440-1681.2007.04800.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Ischaemic‐reperfused Rat Heart by Dimethylamiloride Is Associated With Inhibition of Mitochondrial Permeability Transition

Abstract: 1. The aim of the present study was to assess whether protection afforded by the Na(+)/H(+) exchanger blocker dimethylamiloride (DMA) is associated with inhibition of mitochondrial permeability transition (MPT). The effects of DMA were compared with those of cyclosporine (Cs) A, an inhibitor of MPT. 2. Rat hearts were Langendorff perfused with Krebs'-bicarbonate medium containing 10 mmol/L glucose and were subjected to 25 min no-flow global ischaemia and 30 min reperfusion in the presence or absence of 10 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A delayed pH i recovery has been shown to correlate with inhibition of MPTP opening in IR (Kerr et al, 1999). We and others Prendes et al, 2008) demonstrated that cardioprotection induced by NHE-1-specific inhibitors against IR was associated with inhibition of MPTP opening. Hearts treated with NHE-1 inhibitors demonstrated reduced myocyte injury as shown by decreased low LDH release and greater recovery of cardiac function at reperfusion .…”
Section: Indirect Targeting Of Mptpmentioning
confidence: 97%
See 1 more Smart Citation
“…A delayed pH i recovery has been shown to correlate with inhibition of MPTP opening in IR (Kerr et al, 1999). We and others Prendes et al, 2008) demonstrated that cardioprotection induced by NHE-1-specific inhibitors against IR was associated with inhibition of MPTP opening. Hearts treated with NHE-1 inhibitors demonstrated reduced myocyte injury as shown by decreased low LDH release and greater recovery of cardiac function at reperfusion .…”
Section: Indirect Targeting Of Mptpmentioning
confidence: 97%
“…A detailed discussion of the main principles and advantages/ disadvantages of both methods mentioned above has been provided previously (Halestrap et al, 2004;Javadov and Karmazyn, 2007). The DOG-method is used widely by various groups working in experimental cardiology to study the protective effects of pharmacological and conditional inter- ventions on MPTP opening during IR and HF (Javadov et al, 2005;Ciminelli et al, 2006;Prendes et al, 2008).…”
Section: Mptp Opening In Ischemia/reperfusion and Heart Failure Ischementioning
confidence: 99%
“…The myocytes endeavour to restore intracellular pH by activating NHE1 and this increases intracellular Na + concentration allowing Ca 2+ to enter by reversal of NHE1 [190,191]. Indeed, amiloride derivatives such as cariporide that inhibit NHE1 have been shown to protect the heart from reperfusion injury [192] and, using the Hot-DOG technique, to reduce MPTP opening in situ [193][194][195]. Another protective mechanism that may involve the maintenance of a more acid pH during reperfusion is 'post-conditioning' in which very brief (10 s) intermittent ischaemic periods are included within the first few minutes of reperfusion [196][197][198].…”
Section: Reduced Ca 2+ Loading and Phmentioning
confidence: 99%
“…Heart rate and perfusion pressure were monitored continuously ( 9 ). CsA (0.2 µM) was dissolved in ethanol and added to Krebs-Henseleit solution 13 minutes before the induction of ischemia and continued during reperfusion ( 11 , 12 ). After the required period of I/R, the heart was removed from the cannula, then preserved in 10% formalin for histological studies.…”
Section: Methodsmentioning
confidence: 99%